Marginalized voices in music education - Talbot, Brent C. (Routledge, 2018)
"Marginalized Voices in Music Education explores the American culture of music teachers by looking at marginalization and privilege in music education as a means to critique prevailing assumptions and paradigms. In fifteen contributed essays, authors set out to expand notions of who we believe we are as music educators -- and who we want to become. This book is a collection of perspectives by some of the leading and emerging thinkers in the profession, and identifies cases of individuals or groups who had experienced marginalization. It shares the diverse stories in a struggle for inclusion, with the goal to begin or expand conversation in undergraduate and graduate courses in music teacher education. Through the telling of these stores, authors hope to recast music education as fertile ground for transformation, experimentation and renewal."--Provided by publisher